The Impact of Topic Interest on EFL Incidental Vocabulary Acquisition - Nunung Nurhayati; Arief Styo Nugroho; Puji Siswanto; Obay Jambari; Habib Cahyono; Anatasya Anatasya (Edumaspul: Jurnal Pendidikan, 2024)
This research was conducted to find out whether there is an impact of topic interest on EFL incidental vocabulary acquisition or not. The sample of this research consist of 39 students, 19 students in experimental class and 20 students in control class. The method used in this research was quantitative with Quasi- Experimental design. The data was analyzed by using SPSS 26.0. The result showed that there was an impact of topic interest on EFL incidental vocabulary acquisition. It was proved by the t count value higher than t-table value (-13.419 < -1.734). Thus, Ha was accepted and Ho was rejected. The result of the pre-test mean value for the experimental class is 78.94, while the mean of post-test is 91.84. Therefore, the mean value of students increased 12.9.